Lessons Learned from the Recent Natural Disasters in Indonesia - Sri Prabandiyani Retno Wardani, Agus Setyo Muntohar (2013)
Indonesia has 245 million people located in the world’s largest archipelago on the Ring of Fire who are at risk from earthquakes, tsunamis, volcanoes, and landslides. Earthquakes, tsunamis, and volcanoes occur as a result of ongoing subduction of the Indo-Australian plate in the vicinity of Indonesia. It is one of the seismic sources in this area. High frictional stresses also cause medium earthquakes on the overriding plate that are often observed within and to the south of the island. The megathrust region to the west-northwest of Sumatera and Java has also caused colossal earthquakes, as the region is subject to medium, large, and massive earthquakes. Several major earthquakes recently occurred in Aceh in 2004, Nias in 2005, Yogyakarta, West Java and West Sumatra in 2006, Bengkulu and West Sumatra in 2007, and West Java and West Sumatera in 2009. Some of these were followed by large tsunamis that claimed the lives of hundreds of thousands of people and damaged half a million structures. The social and economic consequences of these earthquakes are tremendous.